Epitaxial grown self-supporting NiSe/Ni3S2/Ni12P5 vertical nanofiber arrays on Ni foam for high performance supercapacitor: Matched exposed facets and re-distribution of electron density. (January 2019) - Tao, Keyu; Gong, Yun; Lin, Jianhua
Abstract: NiSe, Ni3 S2 and NiSe/Ni3 S2 heterostructures with different Se/S ratios were grown on Ni foam (NF) via one-step solvothermal reaction, and they exhibited different morphologies and electrochemical behaviors. Among them, NiSe/Ni3 S2 /NF-1:1 heterojunction (Se/S molar ratio = 1:1) showed the best electrochemical performance, which was associated with its unique morphology of self-supporting nanofiber arrays vertically grown on Ni foam. The epitaxial growth mechanism of the free-standing NiSe/Ni3 S2 nanofibers was investigated and it is related to their matched d spacings. After further phosphorization treatment, Ni12 P5 nanoparticles can grow on the surface of NiSe/Ni3 S2 nanofibers due to their matched exposed facets. The obtained NiSe/Ni3 S2 /Ni12 P5 /NF-1:1 hierarchical nanostructure with a large mass-loading of 8.5 mg cm −2 can provide an ultrahigh areal capacity of 2.04 mA h cm −2 at 10 mA cm −2 (272 mA h g −1 at 1 A g −1 ) with excellent cycling stability. In a hybrid supercapacitor (HSC), 86% of capacity was retained after 5000 charge/discharge cycles at 140 mA cm −2 . The outstanding electrochemical behavior of NiSe/Ni3 S2 /Ni12 P5 /NF-1:1 is probably associated with the re-distribution of electron densities within the heterostructure, and the good electron conductivity of the protective Ni12 P5 nanoparticles on the surface of nanofibers. Furthermore, the phosphorization mechanism of the nickel chalcogenide/NF was primarily explored. Graphical abstract: NiSe, Ni3 S2 and NiSe/Ni3 S2 /Ni foam (NF) heterostructures with different Se/S ratios as well as their phosphorized samples have been synthesized and they exhibit different morphologies and electrochemical behaviors, in which the epitaxial grown self-supporting NiSe/Ni3 S2 /Ni12 P5 /NF-1:1 vertical nanofiber arrays at a large mass -loading of 8.5 mg cm −2 show the best electrochemical performance with an ultrahigh areal capacity of 2.04 mA h cm −2 at 10 mA cm −2 (272 mA h g −1 at 1 A g −1 ) and 86% of capacity retention after 5000 charge/discharge cycles at 140 mA cm −2 . The reason for the outstanding behavior and the epitaxial growth/phosphorization mechanism are explored.fx1 Highlights: NiSe/Ni3 S2 heterostructures with different Se/S molar ratios were grown on Ni foam. Epitaxial growth mechanism of the free-standing NiSe/Ni3 S2 was investigated. NiSe/Ni3 S2 /Ni12 P5 /NF-1:1 provided excellent electrochemical performance. Phosphorization mechanism and re-distribution of electron density were explored.